The Diversity of Causative Agent Associated With Bacterial Diseases on Catfish (Clarias gariepinus) with Molecular Based from Demak, Indonesia - Sarjito Sarjito; A. Harjuno Condro Haditomo; Desrina Desrina; Restiana Ariyati; S. Budi Prayitno (Fisheries and Marine Science Faculty - Jenderal Soedirman University)
Bacterial diseases is frequently occur in catfish culture. The aim of this research was to find out the diversity of causative agent associated with bacterial diseases in catfish based on 16S rDNA gene sequences. The combination between exploratory in the field and experiment, method were applied. Seventeen isolates (D01–D17) were gained from kidney and external wound of moribound catfish with NA and GSP medium that were collected from fish pond of Demak Regency, Indonesia. Based on the postulat results showed that four isolates (D07, D10, D11 and D14) that were caused 10–55% of fishes get sick and 0–30% fishes mortal. On the other hand, there were 13 isolates do not cause both sick and mortality of fish. On the basis of sequence 16S rDNA analysis, the result showed that D07, D10, D11 and D14 were closely related to Aeromonas caviae (96%), Aeromonas veronii (97%.), Plesiomonas shigelloides (97%) and Pseudomonas putida (96%) respectively. The sensitivity test result indicated that these causative agents have not sensitively to some fish drugs test.